TEKNIK MIND MAPING DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH IBTIDAIYAH ADABIYAH II PALEMBANG - Maryamah Maryamah (Ta'dib: Jurnal Pendidikan Islam, 2014)
The use of some different methods, techniques, media, could cover students’ characteristics and students’ final result. One of those techniques is mind mapping. Mind mapping is brain approach technique that allows us to make some notes in a page. By using visual and graphic stimulation, mind mapping provides deeper images. The result of the study showed that: 1) there were 15 (56%) of 27 students from an experimental group/class V.1 were at fair category. 2) there were 16 (59%) of 27 students from control group/class V.3 were at fair category. 3) the comparing test after comparing t value was (to = 4, 8) and t table is (tt.ts.5% = 2, 01 dan tt.ts. 1% = 2, 68). It can be concluded that to is higher than tt; or 2, 01<4, 8<2, 68.  It means that there were a significant difference before implementing mind mapping technique and after implementing it (Ha accepted).